Political modernization and digital democracy: the internet participation of Malaysia domestic citizens to “2021–2022 Malaysian floods” event in public policy process of flood response - Liu, Niwen; Yasin, Megat Al Imran; Alsagoff, Syed Agil; Ng, Chwee Fang; Li, Mengyu (Human Resource Management Academic Research Society, 2023)
In the mid-century, Internet information technology began to flourish worldwide, and a dramatic revolution brought about the Internet information age. The Internet has changed the way of human political life. A staggering number of Internet users began to form a significant force to participate in and influence national politics and public policy. The Internet has transformed traditional public policy processes on a global scale. Citizen participation on the Internet has gained widespread attention in politics, public administration, and public policy issues. The staggering amount of politically relevant information posted by citizens on the Internet has begun to form a significant political force that involves and influences politics and government public policy decisions. This study discusses the Malaysian government’s response to the flood event, the well-known “2021–2022 Malaysian Floods,” to explore the current state of political modernization and digital democracy in Malaysia based on bottom up participation mechanisms of citizens’ Internet involvement in public policy processes. This paper argues that public participation in our public policy through effective Internet will have a broader democratic base and will be closer to the goal of democratic and scientific decision making.